Inguinal Lymphatic Malformation: A Rare Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Lymphatic malformation are most commonly located in regions of confluence of major lymphatic channels, including the neck ( 75%), axilla ( 20%), mediastinum, retroperitoneum, pelvis and groin. We are reporting here a very rare case in which a 15 months old boy presented with a painless lump in the right groin. Preoperative imaging, exploration, macroscopic and microscopic examination of the excised specimen revealed it a case of lymphatic malformation (cystic hygroma). This case is unique in terms of site of presentation. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 62-63